Shovah’s Reality (Re)Construction: A Žižekian Reading of Ideology in Phil Kelly's Farsight - Thoha Arsyad; Mala Hernawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
This research examines the logic behind Shovah's ideology upon the Greater Good and how his fantasy helps him reconstruct his reality in Phil Kelly's novel Farsight. The primary data of this research is obtained by the means of close reading of the novel, notably narration and conversation which concern Shovah and his overall attitude. The analysis of Shovah's ideological journey employs Slavoj Žižek's theory of ideology. The study reveals that the Greater Good acts as an ideological quilt, an empty signifier that unifies particular attributes. However, at the same time, the Greater Good as an ideological quilt is unstable because there is nothing behind it. According to Žižek's theory, Shovah's devotion to the Greater Good can be seen as a process of satisfying the traumatic abyss of the big Other, which is analogous to nothingness. To elude this traumatic abyss, Shovah constructed fantasy, a screen against the desire of the big Other, to keep living in reality.